Incidence of Caesarean Section Delivery in District Sialkot (Medical Forum Monthly, 2024)
Objective: To evaluate the incidence of Caesarean section delivery in District Sialkot.Study Design: Observational / descriptive Study.Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology at Idris Teaching Hospital Sialkot, Islam Teaching Hospital Sialkot, Allama Iqbal Memorial Teaching Hospital Sialkot and number of private hospitals of the Sialkot from January 2015 to July 2016.Materials and Methods: One thousand caesarean section deliveries were included in this retrospective study in the department of obstetrics and gynecology at Idris Teaching Hospital Sialkot, Islam Teaching Hospital Sialkot, Allama Iqbal Memorial Teaching Hospital Sialkot and number of private hospitals of the Sialkot. The charts were reviewed, and age, history of the patient, family history of the caesarean section delivery, date of caesarean section delivery , number of caesarean section delivery, socio economic status, area of the patient, anesthesia used for caesarean section delivery were recorded on designed Performa. The fully informed consent of every patient prior to surgery was recorded. Ethical committee permission of all institutes was taken. The results were analyzed by SPSS version 10. Results: In our study the incidence of caesarean section delivery were maximum (63.3%) 633 cases at the age of 26-30 years and minimum (3.4%) 34 cases at the age of 16-20 years. It was observed that incidence of caesarean section delivery was much higher (51.1%) 511 cases in middle socio economic class as compared to high socio economic group (17.6%) 176 cases and low socio economic group (31.3%) 313 cases. The women belonging to rural area had almost double incidence (70.3%) 703 cases as compared to urban area (29.7%) 297 cases. The incidence was maximum (42%) 420 cases in women having second caesarean section delivery and minimum (10.1%) 101 cases. The incidence was almost double (69.3%) 693 cases in planned C Section delivery as compared to emergency C Section delivery (30.7%) 307 cases. It was also seen that the incidence of C Section delivery was almost double (70.3%) 703 cases under spinal anesthesia as compared to C-Section delivery under general anesthesia (29.7%) 297 cases. Indication of C-Section delivery was maximum (23.7%) 237 cases in previous C-Section and minimum (1.7%) 17 cases of Preeclampsia.Conclusion: The unnecessary caesarean section delivery should be avoided. Proper antenatal care and counseling regarding the planned hospital delivery. Proper diagnosis of labour. Partogram should be maintained for good monitoring of progress of labour especially in patients with previous one caesarean section. Good analgesia and proper fetal monitoring during labour. Expertise in external cephalic version and vaginal breech delivery in good selected cases.